Value co-creation: empirical evidence from the library sector of Sri Lanka - Navaneethakrishnan, S.; Arulanantham, S. (Sri Lanka Library Association, 2015)
One of the challenges of providing standard library services is to create and properly deliver value for readers. In this information era the role of producers and consumers would begin to blur and merge. Users and consumers are now changing their role as prosumers. Value is always co-created between the service provider and the service recipient. In line with this thinking, Value Co-creation could be identified as an active and creative social process, which could be identified and developed as an accelerating factor of Sri Lankan library service through the collaboration between the library and the users. This study aims to determine some evidences of value co-creation activities in Sri Lankan Library and information sector. Using exploratory research method and descriptive research method, this study explains the identified evidences of value co-creation activities relevant to Sri Lankan Library sector. Collections of evidences were obtained from published and unpublished materials and websites of selected Sri Lankan libraries using purposive sampling method in which the evidences were visible and accessible. This study identified the followings as evidences for value co-creation activities. Donation is treated as an accepted acquisition mode of any kind of libraries in Sri Lanka, where the readers and students are donating books. National Library and Documentation Centre receives rare and valuable books collections as donations from the readers of Sri Lanka. National publications were deposited to preserve intellectual rights of the authors. There are exhibitions and courses were organized with the contribution of readers and scholars to improve the information literacy level. School libraries encourage students for publishing hand written magazines which could function as a depositary for the benefit of future students. Library organizations such as SLLA, NILIS are hold research sessions/conferences, for which academic library users and post graduate students are contributing research papers. University libraries have a major role in dissemination of knowledge, and work with faculty users in managing the digital research repository of faculty research output at institutional level. E-mail groups such as library friends were developed by LIS professionals and they were up surged by users by their remarkable support in information sharing. University libraries gather its own reader’s usage on a particular book/periodical by date slips attached with the book. This data has used by other readers as invisible rating of that particular book. Bibliographic and documentation works are carried out by individual readers and students on their own interest. Some library users are active in social media with maintaining blogs on Sri Lanka. Through these evidences it is proved that economic values as well as social values are co-created by the collaboration between the libraries and the users in Sri Lankan library sector. Further this study contributes for an understanding of value co-creation by reinforcing the contexts and conditions where collaborative forms of co-creation might be broaden in Sri Lankan Library and information sector.
Keywords: Value co-creation; Library Services